Enhancement of Secretion and Extracellular Stability of Staphylokinase in Bacillus subtilis by wprA Gene Disruption - Lee, Sang Jun (American Society for Microbiology, 2000)
Staphylokinase (SAK), a polypeptide secreted by Staphylococcus aureus, is a plasminogen activator with a therapeutic potential in thrombosis diseases. A Bacillus subtilis strain which is multiply deficient in exoproteases was transformed by an expression plasmid carrying a promoter and a signal sequence of subtilisin fused in frame with the sak open reading frame. However, the amount of SAK secretion was marginal (45 mg/liter). In contrast, disruption of the wprA gene, which encodes a subtilisin-type protease, strongly promoted the production of SAK in the stationary phase (181 mg/liter). In addition, the extracellular stability of mature SAK was dramatically enhanced. These data indicate a significant role of the wprA gene product in degrading foreign proteins, both during secretion and in the extracellular milieu.